PENGEMBANGAN PRODUKTIVITAS MINUMAN KESEHATAN REMPAH-REMPAH MELALUI GRANULATOR YANG DILENGKAPI FOTO-PASTEURISASI–UV UNTUK MENINGKATKAN IMUN TUBUH - Sutrisno Sutrisno; Mohamad Endy Yulianto; Didik Ariwibowo; Hermawan Dwi Ariyanto; Sri Utami Handayani (Jurnal Pengabdian Vokasi, 2021)
[Development of Ginger-Based Herbal Beverages Using a Granulator and Photo-Pasteurization–UV to Boost Body Immunity] Ginger Emprit is a low-cost Indonesian spice with a high antioxidant content. Micro, Small and Medium Enterprises (MSMEs), such as Gendhis Manes in Ungaran, are the main producers of herbal beverage such as instant ginger drinks. In this UMKM, the traditional method of making instant ginger drink is still used, such as using a traditional stirrer instead of a stirrer. The granulator is used to speed up the production process. Through the use of a granulator or sub-critical extractor machine, as well as photo-pasteurization-uv, this operation intends to boost the productivity of MSME Gendhis Manes.